Removal of Elemental Mercury (Hg(O)) by Nanosized V2O5/TiO2 Catalysts - Lee, Woojin; Bae, Gwi-Nam (American Chemical Society, 2009)
Novel reactive nanosized V2O5/TiO2 catalysts (aerogel, xerogel, and impregnated catalysts) for the removal of Hg(O) and their synthesis methods have been introduced in this research. Aerogel catalyst has the highest surface area among the catalysts synthesized in this research and contained reactive monovanadates on its surfaces resulting in higher reactivity for the Hg(O) removal than impregnated and selective catalytic reduction catalysts. XPS analyses on the surfaces of nanosized catalysts after the removal of Hg(O) suggest that adsorbed Hg(O) oxidatively transformed to HgO by surface vanadates consistent with the Mars-Maessen (mono- and poly vanadates), mechanism. Early column breakthrough has been observed at temperatures above 300 degrees C due mainly to the desorption of Hg(O) from the catalyst surfaces. The decrease in Hg(O) concentration and increase in catalyst content in a column reactor have increased the removal of Hg(O), indicating that the removal is a heterogeneous surface-limited reaction. At 400 degrees C, the catalysts under air flow have shown a higher Hg(O) removal because gas-phase oxygen from the flow could provide an oxygen-rich environment for producing more oxidized vanadate species on their surfaces. No significant difference in the Hg(O) removal between different gas types (nitrogen and air) has been observed at 100 degrees C.
Keywords: FLUE-GAS; HETEROGENEOUS ACTIVATION; OXIDATION; VANADIA; OXIDE; 1,2-DICHLOROBENZENE; PEROXYMONOSULFATE; COMBUSTION; SORPTION; METHANE